2010
DOI: 10.3109/15622975.2010.490273
|View full text |Cite
|
Sign up to set email alerts
|

Altered auditory processing in patients with panic disorder: A pilot study

Abstract: Our results support the hypothesis of an aberrant processing of sensory information in PD patients. This phenomenon may underlie an enhanced responsiveness to anxiety-relevant or irrelevant stimuli possibly increasing PD vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
2
6
0
Order By: Relevance
“…Thus, increases in tph2 in the cDRV may influence encoding of specific sensorimotor events. This hypothesis is consistent with findings that panic disorder patients have altered processing of sensory information …”
Section: Discussionsupporting
confidence: 92%
“…Thus, increases in tph2 in the cDRV may influence encoding of specific sensorimotor events. This hypothesis is consistent with findings that panic disorder patients have altered processing of sensory information …”
Section: Discussionsupporting
confidence: 92%
“…One of the EEG microstates (identical with class A in the present study) was reported to be correlated with negative blood-oxygen-level dependence (BOLD) activations primarily in bilateral superior and middle temporal gyri [18], areas that are implicated in phonological processing in RSNs [19]-[20]. Thus, more percent total time in microstates of class A in the present study may suggest an abnormality in the temporal lobe, which would not be specific for PD but which has been reported in previous structural studies [46][47] or in functional studies of the auditory system [48][49] in patients with PD.…”
Section: Discussionsupporting
confidence: 51%
“…Importantly, our assay distinguishes between the effects of a compound on behavioral modulation (e.g., habituation, sensitivity) and alterations in kinematic performance. Given that deficits in modulation of the mammalian acoustic startle response represent an endophenotype common to many neuropsychiatric disorders (73)(74)(75), future screening with the assay described here can be applied to distinguish between many kinematic and behavioral processes as the primary target of already available drugs, and also can be applied toward the systematic identification of more "behavior-specific" compounds.…”
Section: Conservation Of Neural Substrates Of Learning Between Zebrafmentioning
confidence: 99%